The Role of Caspase-4 and NLRP1 in MCF7 Cell Pyroptosis Induced by hUCMSC-Secreted Factors - Yang Jiao; Linlin Wang; Lin Lu; Jianjun Liu; Xin Li; Hongbo Zhao; Zongliu Hou; Bingrong Zheng (Stem Cells International)
Mesenchymal stem cells (MSCs) are being widely investigated for the development of novel therapeutic approaches for different cancers, including breast cancer, the leading form of cancer in women. Our previous study showed that the factors secreted by human umbilical cord MSCs (hUCMSCs) induced pyroptosis in the breast cancer cell line MCF7 and our RNA sequencing studies revealed an increase in the expression of the pyroptosis-related gene caspase-4 (CASP4) and nucleotide-binding, leucine-rich repeat pyrin domain-containing protein 1 (NLRP1) in pyroptotic MCF7 cells. Cellular pyroptosis can occur via the canonical pathway (involving caspase-1 and NLRP1) or the noncanonical pathway (involving caspase-4). In this study, we first confirmed that the inflammasome complex formed by NLRP1 and ASC is involved in MCF7 cell pyroptosis induced by hUCMSC-CM. Further, we investigated the role of CASP4 and NLRP1 in MCF7 cell pyroptosis induced by hUCMSC-secreted factors using shRNA-mediated transfection of CASP4 or NLRP1 in MCF7 cells. Cytotoxicity analyses revealed that neither CASP4 knockdown nor NLRP1 knockdown could inhibit the hUCMSC-CM-induced pyroptosis in MCF7 cells. Gene and protein expression analysis showed that hUCMSC-CM induced pyroptosis mainly via the canonical pathway in CASP4 knockdown MCF7 cells but mainly via the noncanonical pathway in NLRP1 knockdown MCF7 cells. Our study provides a foundation for further studies aimed at elucidating the precise mechanism underlying hUCMSC-induced pyroptosis in breast cancer cells and aid the identification of potential therapeutic targets for breast cancer.